Characteristics of Arabic Chicken (Gallus turcicus) Egg Flour with Different Drying Methods - Firmansyah, Angga Maulana; Jambang, Nicolays; Hakim, Lukman; Permadi, Selma Noor; Wahyono, Teguh; Rahmawati, Laila; Setiyawan, Ahmad Iskandar; Febrisiantosa, Andi; Fauziyyah, Athiefah (Jurnal Ilmu Pertanian Indonesia, 2025)
Eggs of Arabic chicken (Gallus turcicus) have a high nutritional value and distinct traits, although they have a short shelf-life (about 17 d) and are prone to contamination. To address this issue, drying methods such as oven-drying, spray-drying, and freeze-drying can be employed to convert eggs to flour. This study investigated the physicochemical and microbiological properties of Arab chicken egg flour produced using various drying procedures to give comparative data and aid in the development of novel egg-based products. The study found that different drying processes had substantial (p